Habitus Puri dan Griya untuk Menjaga Keberlanjutan Budaya Bali sebagai Bentuk Etnopedagogi Berkelanjutan - Ida Bagus Weda Wigena; Komang Alit Wahyuni; Ida Bagus Arya Lawa Manuaba; Arif Sobirin Wibowo; Ida Ayu Made Putri Arini (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
Puri is the residence of the Kshatriya dynasty, while Griya is the residence of the Brahmin dynasty. Puri and Griya represent habitus and capital that can serve as arenas for preserving Balinese culture. The purpose of this study is to analyze habitus and capital in Puri and Griya based on Bourdieu's theory of social practice, as well as to analyze cultural inheritance through informal education in Puri and Griya. The research paradigm is qualitative ethnography. The research subjects are one extended Puri and Griya family selected using purposive sampling techniques. The research objects are social practices learned informally. Data collection techniques use participatory observation, in-depth naturalistic interviews, documentation, and FGDs, with semi-structured instruments. Data analysis uses ethnographic techniques, namely triangulation, which includes description, analysis, and interpretation. The essence of the ethnography obtained is that Puri and Griya are a habitus with the power of economic, social, cultural, and symbolic capital. The power of these diverse forms of capital shapes social practices in the form of informal education that both teach and preserve elements of Balinese culture, such as refined Balinese, Old Javanese, Sanskrit, knowledge systems, social organization, religious systems, and the arts.